The Influence of Security, Trust and Price on Puri Mansion Housing Purchasing Decisions - Samudro, Amzad; Raharja, Indra; Hamdan, Hamdan (Dinasti International Journal of Digital Business Management, 2024)
This research aims to analyze the influence of security, trust and price on purchasing decisions for Puri Mansion housing in West Jakarta. The approach used is quantitative-descriptive research, as a result the sample was determined using a non-probability purposive sampling technique. The samples obtained were 160 samples using a web questionnaire technique as a data collection tool. This makes this research choose the SEM-PLS data analysis method with the SmartPLS application. The results of this research provide knowledge that security, trust, and price produce a positive and significant effect on the decision to purchase Puri Mansion housing. This proves how important the factors of security, trust and price are in determining home purchasing decisions. Therefore, the main focus of attention for property business actors is implementing these factors as strategic decision-making actions in the context of effective marketing management in the future, and of course this will be an addition to the latest knowledge for further reliable research